2023
DOI: 10.1371/journal.pone.0284275
|View full text |Cite
|
Sign up to set email alerts
|

The sum of all parts: A multi-level exploration of racial and ethnic identity formation during emerging adulthood

Abstract: According to the 2020 U.S. Census, the multiracial population measured at 33.8 million, nearly a 300% increase from the 2010 U.S. Census. The significant increase is due in part to improvements in measures to categorize this population. However, there is a dearth of research on the factors and processes that affect multiracial identity formation. The researchers investigated the precipitating factors to the formation of multiracial identification. Participants were recruited through social media campaigns. Hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Additionally, older emerging adults in the United States may lose health insurance coverage as they age out of their parents’ health insurance coverage [ 12 ], and indeed, emerging adults have the lowest medical insurance coverage of any age group [ 13 ] and the highest utilization of the emergency department for medical care [ 14 , 15 ]. Minority emerging adults experience this transition differently than their non-Hispanic White peers [ 16 18 ] and have been shown to be at an increased risk for negative physical and mental health outcomes [ 19 ]. While little is known about COVID-19 outcomes in Black American emerging adults with asthma, previous research has shown that COVID-19 exacerbated, rather than alleviated, existing health inequities [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, older emerging adults in the United States may lose health insurance coverage as they age out of their parents’ health insurance coverage [ 12 ], and indeed, emerging adults have the lowest medical insurance coverage of any age group [ 13 ] and the highest utilization of the emergency department for medical care [ 14 , 15 ]. Minority emerging adults experience this transition differently than their non-Hispanic White peers [ 16 18 ] and have been shown to be at an increased risk for negative physical and mental health outcomes [ 19 ]. While little is known about COVID-19 outcomes in Black American emerging adults with asthma, previous research has shown that COVID-19 exacerbated, rather than alleviated, existing health inequities [ 20 ].…”
Section: Introductionmentioning
confidence: 99%